Perceptions of food environments and nutrition among residents of the Flathead Indian Reservation - Carmen Byker Shanks; Selena Ahmed; Virgil Dupuis; Bailey Houghtaling; Mary Ann Running Crane; Mike Tryon; Mike Pierre (BMC, 2020)
Abstract Background Indigenous food systems have been displaced with the emergence of colonization, industrialization, and cultural, economic, political, and environmental changes. This disruption can be seen in marked health and food environment disparities that contribute to high obesity and diabetes mellitus prevalence among Native American peoples. Methods A Community-Based Participatory Research (CBPR) approach was used to document food environment experiences among residents of the Flathead Reservation in rural Montana. Participants were identified using purposive sampling techniques to participate in a survey and a semi-structured interview. Descriptive statistics helped to describe participant demographics, food access variables, and household food security status. Food environment perceptions were analyzed using the constant comparison method among trained researchers. Results Participants completed surveys (n = 79) and interviews (n = 76). A large number participated in federal nutrition assistance programs. Many self-reported experiencing diet-related chronic diseases. Major themes included the community food environment, dietary norms, and food-health connections. Subthemes were represented by perceptions of food environment transitions and the important role of food in familial life. Further, opportunities and challenges were identified for improving community food environments. Conclusions Perceptions of the food environment were linked to strategies that could be targeted to improve dietary quality along a social-ecological model continuum. There is need for skill-based education that directly addresses the time and monetary constraints that were commonly experienced by residents. Coinciding food environment interventions to promote dietary quality that engage community members, store management, and government policy stakeholders are also needed to reestablish healthy Native American food systems and environments within this community.